Excess Molar Volumes and Kinematic Viscosities of Diethylene Glycol + Dimethyl Sulfoxide at T = (298.15, 303.15, 308.15, 313.15 and 318.15) K - Wang, Wenxin; Li, Chunping; Zhang, Na; Li, Meng (Asian Journal of Chemistry, 2013)
Densities (r) and kinematic viscosities (n) for the binary system of diethylene glycol + dimethyl sulfoxide were measured at T = (298.15, 303.15, 308.15, 313.15 and 318.15) K. The density values, which were determined using a capillary pycnometer, were used to calculate the excess molar volumes (VmE). The kinematic viscosity (n) data measured with an Ubbelohde capillary viscometer were used to calculate activation enthalpy (DH*) and activation entropy (DS*) for the viscous flow.